Thermal design and analysis of the SKA SA MeerKAT Digitiser - Moss, Vaughan (Department of Electrical Engineering, 2019)
The Square Kilometre Array Project is a multi-national venture attempting to build the world's largest radio telescope. Australia and South Africa (together with other African countries), will be host to the SKA site. Both countries are building pre-cursor radio telescopes to demonstrate their ability to successfully host the project. Square Kilometre Array South Africa (SKA SA) is currently constructing the MeerKAT Radio Telescope in the Karoo Desert. Radio telescopes are conventionally designed to have the signal Digitiser located in the pedestal of the radio telescope antenna structure to shield the incoming radio signal from being contaminated by the electromagnetic interference (EMI)/radio frequency interference (RFI) noise created by the Digitiser electronics. However, if a Digitiser could be placed near the antenna feed, this would decrease the length of the signal path between the receiver and the Digitiser, which would decrease noise on the signal. The aim of this thesis is to present a viable thermal design for an externally, near-feed mounted, passively cooled Digitiser on the MeerKAT Radio Telescope. This has never been done before. Through calculation, simulation and design iteration this aim was achieved, resulting in an operational Digitiser system which is being used on the MeerKAT Radio Telescope and could potentially also be used in SKA Phase 1.